2018
DOI: 10.1007/s13197-018-3140-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, technological and sensory properties of hamburger made with meat from lambs fed on whole cottonseed

Abstract: The physicochemical composition and the technological and sensory properties of hamburgers made with meat from Ile de France lambs fed on different levels (0, 10, 20, 30 and 40%) of whole cottonseed were studied. The addition of whole cottonseed to the lambs' diets decreased the thiobarbituric acid reactive substances in the lamb meat and altered the physicochemical characteristics of the hamburgers, which were characterised by low lipid ( ), cholesterol ( ) and caloric content ( ). The results regarding cooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the last years, several studies using sheep and goat meats with cooked or precooked products and some products ready to cook have been developed as patties [44][45][46][47], nuggets [48][49][50][51][52][53][54], hamburgers [55,56] or pâté [11,[57][58][59] and others [60][61][62][63]. In the Indian subcontinent (India, Pakistan, Bangladesh, Nepal and Sri Lanka), there are several traditional meat products and recipes using sheep and goat meats, such as Rogan Josh, a lamb meat marinated with Kashmiri chilies, Aab Gosht, a lamb curry cooked in milk, Rista and Goshtaba, a minced lamb meat cooked in mutton stock gravy, Haleem prepared from goat or buffalo meats or Kolhapuri mutton with different curries [64].…”
Section: Cooked or Precooked Prepared Productsmentioning
confidence: 99%
“…In the last years, several studies using sheep and goat meats with cooked or precooked products and some products ready to cook have been developed as patties [44][45][46][47], nuggets [48][49][50][51][52][53][54], hamburgers [55,56] or pâté [11,[57][58][59] and others [60][61][62][63]. In the Indian subcontinent (India, Pakistan, Bangladesh, Nepal and Sri Lanka), there are several traditional meat products and recipes using sheep and goat meats, such as Rogan Josh, a lamb meat marinated with Kashmiri chilies, Aab Gosht, a lamb curry cooked in milk, Rista and Goshtaba, a minced lamb meat cooked in mutton stock gravy, Haleem prepared from goat or buffalo meats or Kolhapuri mutton with different curries [64].…”
Section: Cooked or Precooked Prepared Productsmentioning
confidence: 99%
“…According to Costa et al ( 68 ), diets with 27.51% DM of cottonseed negatively affected the flavor of the meat. Monego et al ( 69 ) showed lower acceptance of burgers when lambs consumed more than 16% cottonseed.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is also cheap if compared to other meat products (Oliveira et al, 2013; Turner et al, 2015). Mainly due to its low‐cost, research has been developed to produce hamburgers from several raw materials (Monego et al, 2018; Queiroga et al, 2020; Tonet et al, 2019; Vahmani et al, 2017; Yousefi et al, 2018) and to create different strategies for increasing its shelf life (Hosseini & Jafari, 2020; Manhani et al, 2018; Sohrabpour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%